‘Smart’ Industrial Relations in the Making? Insights from Analysis of Union Responses to Digitalization in Italy - Gasparri, Stefano; Tassinari, Arianna (Relations industrielles / Industrial Relations, 2020)
How do unions respond to the emerging threats and opportunities posed by digitalization in the sphere of employment relations? What factors account for the focus and varying effectiveness of their responses? This paper seeks to address these questions in the case of Italy—a theoretically interesting case that combines significant digitalization-related challenges, historically strong industrial relations institutions under increasing pressure, and diverse union confederations.From the available evidence, we find that Italian union strategies and demands so far have been primarily focused on interventions at the macro and meso levels, with a view to extending traditional forms of protection—especially sectoral collective bargaining agreements—to deal with the disruptive effects of digitalization. This focus has been coupled with some limited innovation in union agendas and discursive repertoires focused on the micro level of intervention, as well as a shift in union preferences toward inclusion of platform workers and self-employed workers in their constituencies. Whilst highlighting the importance of agential factors, we nonetheless find that the focus and effectiveness of union interventions are crucially shaped by prior institutional legacies and distributions of power resources, as well as by the ideological orientation and strategic capabilities of individual unions themselves.Overall, Italian unions have to date tended to privilege gradual response strategies based on extension and adaptation of existing and established institutions. It remains to be seen whether such adaptive approaches will be sufficient to effectively govern the digital transformation of work or whether more radical institutional experimentation will become necessary. Either way, in order to build smart industrial relations in Italy, unions will have an active role to play.